Integrating coagulation, membrane and photocatalytic oxidation technologies for removal of humic acid from water - Tan, Hsing Loong. (2008)
The research aims to study the feasibility of integrating coagulation / flocculation and membrance micro-filtration together with photocatalytic oxidation process (PCO) to remove HAs from water.